Regulatory and Shari'ah perspectives on sukuk issuance for the implementation of Basel III capital requirements in Islamic banks : a study of Malaysia and UAE - Bello, Nabil
This thesis examines Shari'ah regulatory issues underlying the recent sukuk (Islamic bonds) issuances in Islamic banks for meeting Basel III capital requirements. More than thirty sukuk have been issued in countries such as Malaysia, UAE, Saudi Arabia, Bahrain, etc. but there are several issues underlying these structures such as the most relevant Shari'ah principle, the subordination of sukuk holders, conversion or write-off at point of non-viability, etc. There are a number of frameworks for Basel III sukuk structuring, such as the IFSB-15 Revised Capital Adequacy Standard and other regulatory frameworks of some countries. The frameworks are significantly and different in terms of capital requirements, which may Shari'ah-compliant concerns which led to variations in the implementation of Basel III capital requirements in Islamic banks across different jurisdictions. The study explores the permissibility of Basel III sukuk structures by exploring the relevant documents. In addition, selected sukuk structures were examined from Malaysia and UAE. The analysis was conducted on a multiple-case study design based on Shari'ah sources and opinions of Shari'ah boards and individual scholars. The study seeks to answer the question: How can sukuk be structured to meet both Basel III philosophy and without comprising Shari'ah principles? The structures of sukuk as examined in this study are found to have Shari'ah issues, but almost all the issues raised are already established issues, not because of the issuance of Basel III sukuk. This, however has to do with the differences in the interpretation of Shari'ah from the Malaysia perspective and the AAOIFI cum IFSB perspectives. The Malaysia perspective seems to be more pragmatic in finding ways to implement the Basel III requirements to keep the market moving with the global standards, even if this will mean taking the less recognised (marjuh) point of view. It is found, however, that the Malaysian perspective seems selective in construing Shari'ah adaptation to various practices of sukuk issuance, which has dangers that makes it dilutes the objectives of the Shari'ah and of the particular contracts. On the other hand, the AAOIFI cum IFSB perspectives being more idealistic, is far closer to the classical rulings of the Shari'ah in terms of strictly following the opinions of the majority of the scholars. However, with all this, it is found that only Malaysian sukuk strictly follows the rules set by its regulatory bodies. Some countries have no guidelines and as such, measuring the compliance of the sukuk with their regulatory perspective is not even possible. Some that have the requirements based on the IFBS standards seem not to be very much compliant with their regulatory requirements.